2020
DOI: 10.17582/journal.jahp/2021/9.2.119.131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Chitosan, Nano-Chitosan Supplementation and Different Japanese Quail Lines on Growth Performance, Plasma Constituents, Carcass Characteristics, Antioxidant Status and Intestinal Microflora Population

Abstract: A wide variety of feed additives like prebiotics are recently used in poultry diets as better alternative to antibiotic growth promoters, chitosan is one of those prebiotics. Chitosan is a natural bio-polyaminosacharides, biodegradable and non-toxic biopolymer (Vimal et al., 2013) derived from alkaline deacetylation of chitin from shrimp wastes and fungal biomass (Darwesh et al., 2018). Chitosan has specific bioactivities such as immune-enhancing properties and antibacterial activities (Alishahi, 2014). Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
3
4
0
Order By: Relevance
“…Apart from a plant protein source, broiler chickens fed the diets enriched with nano-chitosan exhibited comparable means of FBW, BWG, and FCR to those fed the control diets, with no significant differences among them (Table 2 ). This result is consistent with the findings of Hassan et al ( 2021 ), who found no positive effect of feeding NCH-fortified (30 or 50 mg/kg) diets on growth performance of Japanese quail. With laying hens, Hamady and Farroh ( 2020 ) reported that feeding diets supplemented with NCH (50 or 200 mg/kg) did not significantly affect rate of egg production, egg weight, and FCR from 23 to 34 weeks of age.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Apart from a plant protein source, broiler chickens fed the diets enriched with nano-chitosan exhibited comparable means of FBW, BWG, and FCR to those fed the control diets, with no significant differences among them (Table 2 ). This result is consistent with the findings of Hassan et al ( 2021 ), who found no positive effect of feeding NCH-fortified (30 or 50 mg/kg) diets on growth performance of Japanese quail. With laying hens, Hamady and Farroh ( 2020 ) reported that feeding diets supplemented with NCH (50 or 200 mg/kg) did not significantly affect rate of egg production, egg weight, and FCR from 23 to 34 weeks of age.…”
Section: Resultssupporting
confidence: 93%
“…According to the current findings, Xu et al ( 2020 ) reported that enriching diets of weaning pigs with NCH (200 or 400 mg/kg) resulted in an increase in plasma concentration of IgG at 28 days of age, but the level of IgM was not affected. In line with our outcomes, Hassan et al ( 2021 ) reported that dietary fortification with NCH (30 or 50 mg/kg) caused a significant rise in plasma concentrations of TAC of Japanese quails compared with the control birds. Consistent also with our results, Hamady and Farroh ( 2020 ) demonstrated that laying hens fed NCH-enriched diets (200 mg/kg) showed a significant reduction in egg yolk contents of MDA in comparison to the control hens.…”
Section: Resultssupporting
confidence: 92%
“…According to Osho and Adeola (2020) , dietary COS improved intestinal health in broiler hens by lessening the detrimental consequences of stress. Furthermore, Japanese quails’ antioxidative state was improved by adding COS and nano chitosan, which also increased catalase activity, a characteristic enzymatic antioxidant in poultry ( Hassan et al, 2021 ). Moreover, COS can help improve nutrition transport ( Chen et al, 2022 ), maintain the intestinal barrier afterward, and minimize cellular apoptosis ( Na et al, 2022 ), converting nutrients into hormones used in steroidogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Guan [6] and Hassan, [7] underscore the biological benefits of chitosan as a feed additive, including antibacterial, antioxidant, cholesterollowering, and immunomodulatory properties. Notably, supplementation with chitosan and nanochitosan has been reported to enhance the antioxidative state of Japanese quails, elevating the activity of catalase (CAT), a key enzymatic antioxidant in poultry [7] Further, research by Xu [8] suggests that Chito oligosaccharide…”
Section: Introductionmentioning
confidence: 99%